Chronic infection perturbs the affinity hierarchy of antiviral B cells - Mirela Dimitrova; Tiago Abreu-Mota; Jonas Fixemer; Weldy V. Bonilla; Anna-Friederike Marx; Min Lu; Karen Tintignac; Anna Lena Kastner; Yusuf I. Ertuna; Marianna Florova; Matias Ciancaglini; Kerstin Narr; et al. (Proceedings of the National Academy of Sciences, 2026)
A key function of the germinal center (GC) reaction consists in the preferential expansion and enrichment of high-affinity B cell clones. Whether and how persistent viral infection thwarts this purpose remains ill-defined. Here, we transferred monoclonal lymphocytic choriomeningitis virus–specific B cells into persistently infected hosts. High-affinity B cells expanded vigorously, forming GCs and abundant antibody-secreting cells. When failing to clear viremia or to drive viral mutational escape, the expanded B cell population contracted, ending in its quasi-complete disappearance from the spleen, a process we termed “attrition.” In stark contrast, low-affinity B cells expanded and persisted irrespective of high viral loads. B cell attrition was associated with phenotypic and transcriptional alterations including a prominent Blimp-1 transcriptional signature in high-affinity GC B cells. Blimp-1-deficient B cells were resistant to attrition, suggesting a B cell–intrinsic process. Moreover, exogenously supplied antibody feedback prevented attrition, suggesting that the latter may have resulted from excessive antigenic stimulation. Our findings suggest that in chronic viral infection, the incessant exposure to overwhelming amounts of antigen perturbs B cell affinity hierarchies by preferentially dysregulating high-affinity B cells.